2020
DOI: 10.33314/jnhrc.v17i4.1559
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Regarding Pubertal Health among Adolescent Girls

Abstract: Background: Adolescence is a critical period and is associated with physical and psycho-social changes induced by puberty, which builds personality, behaviour, and future health of the adolescents. Thus, the aim of the study was to find out the knowledge and attitude regarding pubertal health of adolescence girls.Methods: A descriptive cross sectional study was conducted in Bharatpur Metropolitan City’s secondary level schools. A total of 183 adolescent girls were selected using probability simple random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, in a similar study conducted among adolescents in Bharatpur, Chitwan, 89% had an unfavorable attitude toward pubertal changes [5]. In another study, adolescents showed that 52% had a negative attitude toward it [11]. A descriptive study of the Ambala district showed a majority of pre-adolescent girls and boys (75%) had below-average knowledge regarding pubertal changes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in a similar study conducted among adolescents in Bharatpur, Chitwan, 89% had an unfavorable attitude toward pubertal changes [5]. In another study, adolescents showed that 52% had a negative attitude toward it [11]. A descriptive study of the Ambala district showed a majority of pre-adolescent girls and boys (75%) had below-average knowledge regarding pubertal changes.…”
Section: Discussionmentioning
confidence: 98%
“…These questionnaires were developed by reviewing related works of literature thoroughly and were validated before conducting the study. The sample size was calculated using the relation: n = (z)2 p ( 1 -p ) / d2 where n = sample size; z = level of confidence according to the standard normal distribution; p = estimated proportion of the population that presents the characteristic and d = tolerated margin of error [11,12]. The study was conducted only after approval from the Institutional Review Committee of Nagarik College of Health Science.…”
Section: Methodsmentioning
confidence: 99%
“… 28 Lack of knowledge and experience, the influence of peers, and high risk behaviors in teenagers; underscores the crucial role of health care professionals. 29 , 30 Early motherhood is be viewed as one of significant public health concerns and is examined by obstetricians and gynecologists, pediatricians, child psychologists, sociologists, family doctors, and nurses. 19 Providing high quality services involves awareness of the requirements of adolescent moms, their problems and talents.…”
Section: Introductionmentioning
confidence: 99%